PERKAWINAN ANTAR NEGARA DI INDONESIA BERDASARKAN HUKUM PERDATA INTERNASIONAL DAN HUKUM ISLAM - Dholy Fahri Akbar; Milfa Masitha; Bella Sultana Balqis (SYARIAH: Journal of Islamic Law, 2021)
Marriage is a legal event if the marriage is a legal marriage. The rapid development of science and technology has an influence on the ease of relations between human beings, between ethnic groups, and between countries in all aspects of life. One of the effects is the occurrence of mixed marriages between spouses of different nationalities, including Indonesian workers and workers from other countries. Marriages of different nationalities often cause problems, especially with regard to the process of registering a marriage that will take place, whether in the country of origin of the prospective husband or in the country of origin of the prospective wife. The procedure for marriage between countries according to international civil law explains that the marriage rules for couples of different nationalities, returned to each partner will use the law of the country of the prospective husband, or use the law of the country of the prospective wife.